Ligand-free all-inorganic metal halide nanocubes for fast, ultra-sensitive and self-powered ozone sensors. Issue 7 (7th June 2019) - Brintakis, K.; Gagaoudakis, E.; Kostopoulou, A.; Faka, V.; Argyrou, A.; Binas, V.; Kiriakidis, G.; Stratakis, E.
Abstract : Quick and cost-effective fabrication of metal-halide nanostructure ozone sensors. Abstract : Ligand-free all-inorganic lead halide nanocubes have been investigated as ozone sensing materials operating at room temperature. It is found that the nanocubes, crystallined in the orthorhombic CsPbBr3 structure, can operate at room temperature, be self-powered and exhibit high sensitivity and remarkable repeatability. More importantly, they demonstrate higher sensitivity (54% in 187 ppb) and faster response and recovery times compared to hybrid lead mixed halide perovskite (CH3 NH3 PbI3− x Cl x ) layers, which is the only lead halide perovskite material tested for ozone sensing, to date. Following the exposure to an ozone environment, the stoichiometry and the morphology of the nanocubes remain unaltered. The facile and easy fabrication process together with the high responsivity and stability to the ozone environment makes the bare CsPbBr3 nanocubes a promising material for sensing applications. The sensing properties of the nanoparticulate metal halides presented here provide new exciting opportunities towards engineering reliable and cheap sensing elements for room-temperature operated and self-powered sensors.